Análise da reforma brasileira do ensino médio de 2017 à luz da escola unitária de Gramsci - Ferrari, Julie Fernanda (2020)
This dissertation has as its theme the new reform of high school, which is analyzed in the light of Gramsci's unitary school proposal. Considering that the referred reform was carried out in the government of Michel Temer by Provisional Measure 746/2016 and became Law 13,415 / 17, both the law and the provisional measure were the object of this research. The investigation sought to problematize the proposal for comprehensive training present in the law in question, which alters the structure of high school, and how it approaches or distances itself from Antonio Gramsci's unitary school proposal. The methodology used was bibliographic and documentary research, with a qualitative focus. Bibliographically, researchers Saviani, Ribeiro, Freitas, Da Silva, Ferretti, Fatorelli, Orso etc. were identified. as a basis for the study of High School Reform, and as the foundation of the exhibition on Gramsci's unitary school, the authors Monasta, Mochcovitch, Martins, Dore, Liguori, Coutinho, Ciavatta, Nosella, in addition to Gramsci himself. Documentally, three documents are presented and analyzed: Law 13,415 / 17, MP 746/2016 and Common National Curriculum for High School. The results achieved revealed that the reform may increase social inequalities, since it is only interested in training cheap labor in the market, commercializing and outsourcing education, in addition to expanding the dichotomy between doing and knowing in the teaching process- school learning, which is very different, if not the opposite, from the education proposal present in the legacy left by Antonio Gramsci in his notebooks and letters from prison, and even in texts from “youth”, in the period prior to the arrest.